Community-Based Digital Tourism Communication: Strategies for Promoting Tourism Destinations in Buton Regency - Dian Faradika Dian; Harry Fajar Maulana; Ansar Suherman (Jogjakarta Communication Conference (JCC), 2026)
The rapid expansion of digital communication technologies has transformed the way tourism destinations are promoted and represented.  In contemporary tourism contexts, digital platforms not only function as promotional tools but also shape destination narratives and influence tourist perceptions. This study aims to analyze the implementation of community-based digital tourism communication strategies in Buton Regency and to examine the role of local communities in supporting tourism promotion in the digital environment. This research employed a qualitative case study approach to explore communication practices within the tourism governance structure of Buton Regency. Data were collected through in-depth interviews with key tourism stakeholders, digital observation of social media activities, and analysis of relevant documentation. The data were analyzed using thematic analysis, involving stages of initial coding, focused coding, and theme development to identify patterns in digital tourism communication practices. The findings reveal that digital tourism communication in Buton Regency is primarily conducted through social media platforms such as Instagram, TikTok, and official tourism websites. Government institutions play an important role in establishing policy frameworks and coordinating promotional activities, including the regulation of posting frequency and content production processes. At the same time, local communities contribute to tourism promotion through participatory activities, independent social media communication, and collaboration in promotional content production. This interaction creates a hybrid communication ecosystem in which institutional promotion and community-generated narratives complement each other. The study concludes that community participation enhances the authenticity and credibility of digital tourism communication, thereby supporting destination visibility and strengthening the potential for sustainable tourism development. These findings highlight the importance of collaborative digital communication strategies that integrate government initiatives with community-based participation in tourism promotion.